Dental Caries Spectrum Profile and Dental Visits by Preschool Children: Application of Andersen's Model - Fernanda Vieira Almeida; Laís Anschau Pauli; Marina Sousa Azevedo; Vanessa Polina Pereira Costa; Marília Cunha Maroneze; Marília Leão Goettems (Association of Support to Oral Health Research (APESB), 2024)
Objective: To estimate the frequency of preschool children who attended a dental visit and identify associated factors. Material and Methods: A cross-sectional study was conducted with children aged 2-5 years enrolled in preschools (n=200) in southern Brazil. Parents/guardians completed a questionnaire, and oral exams were performed using the CAST instrument. The outcome was whether the children had consulted a dentist in their lifetime. Andersen's behavioral model was applied to assess associated factors, including predisposing factors (sex, age, maternal education), enabling factors (family income), need factors (dental caries severity, dental pain, oral health-related quality of life (OHRQoL), and oral hygiene habits), and psychosocial factors (dental fear). Associations were tested using Poisson's regression, obtaining the prevalence ratio (PR) and 95% confidence interval (CI). Results: The majority of the children had never visited a dentist (71%; n=141), while 15% (30) had done so for prevention and 14% (29) for oral health problems. Need factors associated with having consulted a dentist included severe dental caries (PR=3.11; 95%CI=1.85-5.20), dental pain (PR=2.04; 95%CI=1.32-2.17), toothbrushing performed by parents (PR=1.99; 95%CI=1.05-3.77), and presence of an impact on OHRQoL (PR=1.87; 95%CI=1.21-2.89). The psychosocial factor of the absence of dental fear (PR=2.28; 95%CI=1.45-3.59) was also associated with the outcome. Conclusion: Most preschool children have never visited a dentist. Using a dental service was associated with both need and psychosocial factors.